Utilizing a social network site in English literature learning - Abdul Rahman, Azrina (2013)
The purpose of this study is to examine how a Social Network Site, Facebook could promote English literature learning. The study also aims to identify stances and levels of understanding that students adopt in their literary responses via Facebook as well as to examine how Facebook promotes English literature learning among students. Currently, there is still a need for researches on the utilization of Social Network Sites in a school setting as most literature focuses on the tertiary institution. Ten students from an urban secondary school in Johor Bahru, Malaysia were involved in this study across 10 weeks. A total of 43 literary responses via Facebook were analyzed and categorized based on An Instrument for Measuring Reader Stance on an Efferent or Aesthetic Continuum and An Instrument for Rating a Reader’s Level of Understanding. Emerging themes that surfaced suggested that Facebook is a potentially useful tool in promoting English language literature learning. In addition, this study found a unique occurrence termed as Multiple Levels of Understanding that exist within a literary response. Ten interviews were analyzed and interesting perceptions in relation to students’ experiences in utilizing Facebook for English literature learning were identified. This study highlights that Social Network Sites could potentially be useful and effective in English literature learning in a school setting.